MOTIVASI BELAJAR MANDIRI TERHADAP HASIL BELAJAR OPERASI BILANGAN BULAT PADA SISWA SMP - Florentina Arni Alus; Sofia Sa'o; Stefanus Notan Tupen (Program Studi Pendidikan Matematika, 2023)
This study aims to determine the effect of independent learning motivation on the learning outcomes of integer operations in students of Ende Christian Private Junior High School. This type of research is quantitative. The population in this study was all students of Ende Christian Private Junior High School while the sample in this study was 23 students of grade VII B ENDE Christian Junior High School. Data collection was carried out using two questionnaire instruments and a test of learning outcomes of integer operations. The results of descriptive statistical analysis showed that the self-learning motivation of grade VII B students of Ende Christian Private Junior High School was categorized as medium with an average score of 59.00 with the highest score of 80 and the lowest score of 34 while the learning outcomes of integer operations of Ende Christian Private Junior High School were categorized as lacking an average score of 62,22 with the highest score of 90 and the lowest score of 40. While inferential statistical analysis obtained independent learning motivation had a significant effect on the learning outcomes of integer operations in grade VII B students of Ende Christian Private Junior High School by 56.1%.